ChemInform Abstract: Enantioselective Nickel‐Catalyzed Hydrocyanation Using Chiral Phosphine‐Phosphite Ligands: Recent Improvements and Insights. Issue 9 (February 2016) - Falk, Anna; Cavalieri, Alberto; Nichol, Gary S.; Vogt, Dieter; Schmalz, Hans‐Guenther
Abstract: This method allows Markovnikov‐like addition of HCN to vinylarenes in good to high yields and with excellent enantioselectivities.